Mechanism of Hsp104/ClpB inhibition by prion curing Guanidinium hydrochloride - Kummer, Eva; Oguchi, Yuki; Seyffer, Fabian; Bukau, Bernd; Mogk, Axel (FEBS letters, 2013)
The Saccharomyces cerevisiae AAA+ protein Hsp104 and its Escherichia coli counterpart ClpB cooperate with Hsp70 chaperones to refold aggregated proteins and fragment prion fibrils. Hsp104/ClpB activity is regulated by interaction of the M-domain with the first ATPase domain (AAA-1), controlling ATP turnover and Hsp70 cooperation. Guanidinium hydrochloride (GdnHCl) inhibits Hsp104/ClpB activity, leading to prion curing. We show that GdnHCl binding exerts dual effects on Hsp104/ClpB. First, GdnHCl strengthens M-domain/AAA-1 interaction, stabilizing Hsp104/ClpB in a repressed conformation and abrogating Hsp70 cooperation. Second, GdnHCl inhibits continuous ATP turnover by AAA-1. These findings provide the mechanistic basis for prion curing by GdnHCl.
Gesehen am 30.06.2021